Suomalaisista taikamerkeistä : kansatieteellinen tutkielma - Haltsonen, Sulo (Kansatieteellinen arkisto, 1937)
Deutsche Referate.
Keywords: kansatiede; merkit; semiotiikka; magia; symbolit; karjanhoito; historia; heinänkorjuu; suomalaiset; rakennusperinne; kansanusko; taikausko; viljankorjuu; sadonkorjuu; työvälineet; Suomi; Etelä-Pohjanmaa; Pyhämaa